Leveraging university-industry partnerships to optimise postgraduate nursing education - Karen A. Theobald; Robyn Fox; Christine Burridge; Bernadette Thomson; Amanda Fox (BMC Nursing, 2023)
Abstract Background Industry and higher education sectors devote considerable, but independent resources to deliver postgraduate nursing education. This leads to duplication, uncertainty among students, and critical gaps in nursing education. Establishing and sustaining meaningful partnerships between invested university and industry stakeholders can strengthen workforce capability and improve patient care. Methods To evaluate the feasibility and effectiveness of using a University-Industry Integration Framework to develop a postgraduate nursing education program. Prospective mixed methods cohort study (STROBE). A co-design approach, using an established University-Industry Integration Framework, leveraged expert stakeholder partnerships to contextualise knowledge and service need for developing a postgraduate education program for cancer care nurses. Results All participants (n = 46) were 100% satisfied with the online resources, support, and communication processes applied. Qualitative data generated three major analytical interpretations (reciprocity, flexible adaptations, authentic learning), highlighting the experiences and connections and how the partnership evolved. Program participants (n = 15) undertook a six-week cancer education program with eight responding to the survey with overwhelming satisfaction (100%), increasing their knowledge and skills. While barriers were evident, three quarters (n = 6) indicated these were addressed and enabled progress in the program. However, 63% (n = 5) were not satisfied with the program workload. Conclusions University and industry partners can apply the University-Industry Integration Framework and deliver a successful postgraduate education program for cancer care services. Within a co-design partnership it is possible to develop strategies and processes to overcome barriers and deliver a program for mutual benefit. The culmination of this successful education program has enhanced collaborations between partners and likely will sustain the offering of future co-design endeavours.